A critical thinking activity for communication classrooms. Issue 2 (3rd April 2017) - Williams, Ann E.
Abstract : Courses: This semester long activity can be employed in any communication classroom and is designed particularly to provide first-time graduate student instructors (GSIs) with a theory-based assessment tool. As such, the article is appropriate for graduate-level pedagogy classes. Objective: To introduce a theory-based, critical thinking activity that can be applied in communication classes to enhance students' mastery of course content at a basic level while also deepening understanding of the learning process promoted through higher levels of cognition.